Systematic Review of the Influence of Antipsychotics on the Blood Oxygenation Level-Dependent Signal of Functional Magnetic Resonance Imaging - H. Roder, C.; Dieleman, S.; M. van der Veen, F.; Linden, D. (Current Medicinal Chemistry, 2013)
Functional Magnetic Resonance Imaging (FMRI) is a non-invasive technique for brain mapping and mostly performed using changes of the blood-oxygen-level-dependent (BOLD)–signal. It has been widely used to investigate patients with schizophrenia. Most of the studies examine patients treated with antipsychotic drugs, although little is known about the effects of these drugs on the BOLDsignal. Here we examined studies of patients with schizophrenia treated with different antipsychotics to address the question whether and to what extent antipsychotic drugs in themselves produce BOLD-signal changes. We performed a PubMed-search for the period from 1999 until January 2012 with the search items “schizophrenia” and “Magnetic Resonance Imaging” and “Antipsychotic Agents; or “Magnetic Resonance Imaging” and “Antipsychotic Agents”; or “schizophrenia” and “Antipsychotic Agents” and “FMRI”. We extracted articles that examined at least two patient groups with different treatments, or patients examined on different medications at different times and that provided information about drug effects. No common effect of antipsychotics on BOLD-signal was found. However, based on the results for different antipsychotics (haloperidol, olanzapine, quetiapine and risperidone) we found evidence that the affinity to the dopamine (DA) D2-receptor may influence BOLD-signal.
Keywords: BOLD